2007
DOI: 10.1212/01.wnl.0000259521.14704.a8
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab reduces visual loss in patients with relapsing multiple sclerosis

Abstract: Natalizumab reduces visual loss in patients with relapsing multiple sclerosis. Low-contrast acuity testing has the capacity to demonstrate treatment effects and is a strong candidate for assessment of visual outcomes in future multiple sclerosis trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 31 publications
3
112
0
1
Order By: Relevance
“…In the SENTINEL trial, the combination of natalizumab plus IFN-b-1a (natalizumab: 300 mg, intravenous infusion, once every 4 weeks; IFN-b-1a 30 mg, intramuscular injection, once weekly) was compared with placebo plus IFN-b-1a [Rudick et al 2006]. Both trials demonstrated the efficacy of natalizumab treatment in reducing relapse rate, visual loss, disease progression and occurrence of new magnetic resonance imaging (MRI) lesions in MS [Radue et al 2010;Havrdova et al 2009;Balcer et al 2007;Miller et al 2007]. …”
Section: Safety and Efficacymentioning
confidence: 99%
“…In the SENTINEL trial, the combination of natalizumab plus IFN-b-1a (natalizumab: 300 mg, intravenous infusion, once every 4 weeks; IFN-b-1a 30 mg, intramuscular injection, once weekly) was compared with placebo plus IFN-b-1a [Rudick et al 2006]. Both trials demonstrated the efficacy of natalizumab treatment in reducing relapse rate, visual loss, disease progression and occurrence of new magnetic resonance imaging (MRI) lesions in MS [Radue et al 2010;Havrdova et al 2009;Balcer et al 2007;Miller et al 2007]. …”
Section: Safety and Efficacymentioning
confidence: 99%
“…The large phase 3 trial of natalizumab versus placebo also identified a better outcome for natalizumab-treated patients in terms of visual function [18] and health-related quality of life [19].…”
Section: Clinical Efficacymentioning
confidence: 97%
“…Natalizumab was initially approved for the treatment of relapsing multiple sclerosis (MS) [15][16][17][18] ; however, the drug was later removed from the market after 3 cases of progressive multifocal leukoencephalopathy (PML), a serious infection of the central nervous system caused by the John Cunningham (JC) virus, occurred [19,20] . The efficacy of natalizumab for induction and maintenance of remission in moderate to severely active CD was established in several randomized clinical trials [21] , including ENACT [22] and ENCORE [23] .…”
Section: Anti-integrinsmentioning
confidence: 99%